The Effect of Service Quality, Customer Satisfaction, and The Moderating Role of Brand Switching Costs on Telkom's Indihome Consumer Loyalty - Aenul Yaqin (Eastasouth Institute, 2022)
At present, the internet has been one of the necessities of the Indonesian citizen. The communities access the internet through subscription to internet service providers. One of the internet providers is Indihome Telkom, the fare of Indihome Telkom is providing the most expensive cost and the lowest internet speed among the other internet providers. This research is on to analyze the influence of service quality, consumer satisfaction, and the role of moderation of the switching cost on consumer loyalty. The sample used in this research is Indihome Telkom's Internet consumer. The data collection method in this research is a purposive sampling method with the respondents acquired are 300 people. The criteria of respondents determined in this research are subscribed consumers of Indihome Telkom Internet with a minimum subscription period of three months, located on Java Island and in the age of 18 years-old and above. The data were collected using questionnaires that distributed online. The analysis techniques used are simple and multiple linear regressions. The results of this study discovered that the satisfaction has a positive influence towards the consumer loyalty, service quality has a positive influence towards customer satisfaction, service quality has a positive influence towards consumer loyalty, switching cost is positively influencing the consumer loyalty and switching cost also conceive another role as the moderator of the correlation between consumer satisfaction and consumer loyalty.